ANALISIS DAMPAK YANG MEMPENGARUHI KINERJA GURU - Putri, Rizka Oktavia Yunia; Tahwin, Muhammad (STKIP Pesisir Selatan, 2025)
Teachers are educators who are the spearhead of a school's success in achieving its vision and mission. To achieve this, an analysis of motivation, competence, and the work environment that impacts changes in teacher performance at MA YSPIS Gandrirojo needs to be conducted. The study population involves all teachers at MA YSPIS Gandrirojo. Saturated sampling was used as the sampling technique with a total of 56 teachers. Multiple linear regression analysis serves as the analytical technique used in this study. The findings of this study indicate that the variables of motivation, competence, and work environment partially have a positive but insignificant relationship with the performance of teachers at MA YSPIS Rembang. The determination test shows that 22.8% of the variation in the performance of MA YSPIS Gandrirojo teachers can be explained by the variation of the three independent variables, namely motivation, competence, and work environment. Meanwhile, the remaining 77.2% is caused by other factors that were not examined in this study. The three factors studied are capable of improving teacher performance but are not the main factors in its enhancement, so the relevant management needs to implement strategies that encompass other factors that may impact teacher performance.